Indigenous Cities. - Porter, Libby (Palgrave Macmillan, 2020)
The historical origins of thousands of cities around the world, many of them cities from where mainstream theory and urban scholarship emanates, lie in dispossession and genocide of Indigenous peoples. Yet this foundational dimension of urbanisation is often simply missing from urban scholarship. Thinking about the city as an Indigenous place is to call for a more truthful and accurate account of what cities are, how they have come to be, and what work they do in securing colonial expansion and erasing Indigenous belonging. Focusing specifically on settler-colonial contexts, this chapter reveals key dimensions for thinking about how cities are Indigenous places, the ways cities are knitted into the structures of settler-colonial domination, and their vital importance for all our futures.
Keywords: Urbanisierung; Stadtgeschichte; Stadtforschung; Kolonialismus; Siedlungsgeschichte; Verdrängung; Indigener Ort; Ureinwohner; Genozid